INNOVATIVE HR MANAGEMENT: NECESSITY AND METHODS OF APPLICATION - Malikova, Dilrabo; Khudoiberdieva, Maftunabonu (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The paper deals with the concept of innovative HR management, also in paper the circumstances and procedure for introducing innovations into personnel work are presented. By analyzing innovative methods and technologies used in modern organizations, the need to create and implement innovations in personnel management is proven.